The shift in significance of having multiple-partnerships relationship to masculinity, then and now - Sithole, Ripfumelo (My University, 2018)
Multiple-partnerships are a common practice in Giyani. These partnerships are often associated with ‘traditional African culture’ and there is a close connection made between history and culture to justify multiple partnerships. The research aims to gather information about multiple-partnerships and their significance to masculinity in present day Giyani. In doing this, the research examines what multiple partnerships are now, in relation to what they were historically, and how this history is being reinvented to justify current practices. The research also examines the extent to which the multiple-partnerships trend is connected and/or disconnected to the socio-economic circumstances of actors. Although I recognize the contribution of HIV/AIDS studies in explaining multiple partnerships and their consequences, namely how they contribute to the spread of HIV/AIDS and sexually transmitted infections, I argue that they do not study multiple partnerships in entirety. What is problematic is that these studies reduce multiple-partnerships to the idea that they are the driving forces of HIV/AIDS in South Africa, and with that immediately consider them as negative and pathological. My thesis thus points to the necessity to locate contemporary multiple-partnerships trend within the context of historical and cultural processes. I have used qualitative-ethnographic research method for my study which entailed semi-structured interviews as the primary methodological approach, focus group interviews and participant observation.
University of the Witwatersrand School of Social Sciences Department of Anthropology Research Dissertation